Surgical Management Of Fish Hook In Indian Flap-Shelled Turtle (Lissemys Punctata) - Charde, Prajakta; Dighule, Bharat; Kate, Mayur; Thorat, M.G.; Jadhao, P.T.; Raulkar , R.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Indian flapshell turtle (Lissemys punctata) is a fresh water species of turtle found all over Asia. Fishing activity has played a very significant role in endangering the existence of fresh water turtles in the world. This is especially true in accidental capture of turtles which get entangled with fish hook and without quick treatment it can result into death of turtle (Moraes-Neto et al., 2003).